Ring-Expansion Reactions of Binaphthyl Azepines and Ferrocenophanes through Metal-Catalyzed [1,2]-Stevens Rearrangements - Harthong, Steven; Bach, Renaud; Besnard, Céline; Guénée, Laure; Lacour, Jérôme (Synthesis, 2013)
Enantiopure binaphthyl azocines can be prepared in a single step via the direct copper-catalyzed reaction of binaphthyl azepines and α-diazo carbonyl reagents. The [1,2]-Stevens rearrangement is general (61–93% yields) and can be extended to [3]ferrocenophanes; similar reactivity in favor of the products of ring expansion is obtained with these ferrocene derivatives (80–96% yields).
Keywords: azepine; azocine; diazo ester; ferrocenophane; [1,2]-Stevens rearrangement